Die Landwirtschaftspolitik der sowjetischen Besatzungmacht auf dem Gebiet des sog. westlichen Weißrußlands in den Jahren 1939-1949 [The agricultural policy of the Soviet occupying power in the territory of the so-called Western Belarus in the years 1939-1949] - Bonusiak, Włodzimierz (Studia Historiae Oeconomicae, 2001)
This article is the first attempt in Polish historiography to characterize a period of the economic policy of the USSR in the territories that were in the Soviet occupation zone after September 28, 1939. Although it refers only to the areas of the so-called Western Belarus, it allows conclusions to be drawn about the entire territory that came under Soviet administration. This is due to the fact that the actual policy was determined by Moscow, not by Minsk or Kiev. The source material for this report was mostly documents from the Political Bureau of the Central Committee of the Communist Party of Belarus (CCPC).